Cerebral cortex swelling in V180I genetic Creutzfeldt–Jakob disease: comparative imaging study between sporadic and V180I genetic Creutzfeldt–Jakob disease in the early stage. Issue 1 (31st December 2023) - Muroga, Yuki; Sugiyama, Atsuhiko; Mukai, Hiroki; Hashiba, Jun; Yokota, Hajime; Satoh, Katsuya; Kitamoto, Tetsuyuki; Wang, Jiaqi; Ito, Shoichi; Kuwabara, Satoshi
ABSTRACT: The most common genetic Creutzfeldt-Jakob disease (gCJD) in Japan is caused by a point mutation in which isoleucine replaces valine at codon 180 of the prion protein ( PrP ) gene (V180I gCJD). Evidence suggests that cerebral cortex swelling, which appears as abnormal hyperintensities on diffusion-weighted imaging (DWI), is a characteristic magnetic resonance imaging (MRI) finding of V180I gCJD. However, no study has directly compared the MRI findings between V180I gCJD and sporadic CJD (sCJD). The current study, therefore, aims to clarify the imaging features of V180I gCJD, which would lead to prompt genetic counselling and analysis of the PrP gene, particularly focusing on cerebral cortex swelling. We included 35 patients with sCJD ( n  = 23) or V180I gCJD ( n  = 12). Cerebral cortex swelling on T2-weighted imaging (T2WI) or fluid-attenuated inversion recovery (FLAIR) wherein abnormal cortical hyperintensities were observed on DWI, and the distribution of grey matter hyperintensities on DWI were visually evaluated. V180I gCJD patients had significantly more cerebral cortex swelling (100% vs. 13.0%, p  < 0.001), an overall correct classification of 91.4%, and parahippocampal gyrus hyperintensities on DWI (100% vs. 39.1%, q  = 0.019) than sCJD patients. Cerebral cortical hyperintensities on DWI with swelling on T2WI or FLAIR are characteristic imaging findings of V180I gCJD and are useful for differentiating it from sCJD.